Improved Lorenz-Mie Look-Up Table for Lidar and Polarimeter Retrievals - Chemyakin, Eduard; Stamnes, Snorre; Burton, Sharon P.; Liu, Xu; Hostetler, Chris; Ferrare, Richard; Cairns, Brian; Dubovik, Oleg (Frontiers in Remote Sensing, 2021)
Lidar and polarimeter aerosol microphysical retrievals require calculating single-scattering properties that are computationally expensive. One of the easiest ways to speed up these calculations is to use a look-up table. Two important currently available look-up tables were created about 15 years ago. Advancements in modern computational hardware allows us to create a new look-up table with improved precision over a larger range of aerosol properties. In this new and improved Lorenz-Mie look-up table we tabulate the light scattering by an ensemble of homogeneous isotropic spheres at arbitrary wavelengths starting from 0.355 mum. The improved look-up table covers spherical atmospheric aerosols with radii in the range of 0.001-100 mum, with real parts of the complex refractive index in the range of 1.29-1.65, and with imaginary parts of the complex refractive index in the range of 0-0.05. We test twelve wavelengths from 0.355 to 2.264 mum and find that the elements of the normalized scattering matrix as well as the asymmetry parameter, the aerosol absorption, backscatter, extinction, and scattering coefficients are precise to within 1% for 99.99% of cases. The look-up table together with C++, Fortran, Matlab, and Python codes are freely available online.